2014
DOI: 10.13073/fpj-d-13-00069
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Woods from Three Native Fast-Growing Species in a Secondary Forest in South Kalimantan, Indonesia

Abstract: Growth characteristics and basic wood properties of three native fast-growing species, terap (Artocarpus elasticus Reinw. ex Blume), medang (Neolitsea latifolia (Blume) S. Moore), and balik angin (Alphitonia excelsa (Fenzel) Reissek ex Benth), were investigated. All three species are grown in a secondary forest in South Kalimantan, Indonesia. No significant correlations between growth characteristics (stem diameter and tree height) and stress-wave velocity of the stems were found. The mean basic density (BD) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
2
9
0
3
Order By: Relevance
“…4). The results obtained in the present study were similar to those obtained in research on other tropical hardwood species (Ishiguri et al 2012b, Makino et al 2012, Istikowati et al 2014. Furthermore, as shown in Table 2, no significant differences in basic density were found among growth categories.…”
Section: Effects Of Radial Growth Rate On Anatomical Characteristics supporting
confidence: 90%
See 2 more Smart Citations
“…4). The results obtained in the present study were similar to those obtained in research on other tropical hardwood species (Ishiguri et al 2012b, Makino et al 2012, Istikowati et al 2014. Furthermore, as shown in Table 2, no significant differences in basic density were found among growth categories.…”
Section: Effects Of Radial Growth Rate On Anatomical Characteristics supporting
confidence: 90%
“…The wood properties of these species have been investigated by many researchers (Wahyudi et al 1999, Honjo et al 2005, Ishiguri et al 2007, 2012a, Kojima et al 2009a, b, Makino et al 2012, Nugroho et al 2012, Darmawan et al 2013). On the other hand, Istikowati et al (2014) examined growth and wood properties in less-utilized-fastgrowing tree species found in a secondary forest naturally regenerated in South Kalimantan, Indonesia. Istikowati et al (2014) found that wood properties might be improved by tree breeding programs for wood quality in these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other previously unutilized fast-growing tree species have also been planted to increase wood resources . The Southeast Asian region is home to many fastgrowing tree species, typically found in secondary forests after shifting cultivation (Suzuki 1999ab, Adi et al 2014, Istikowati et al 2014. However, utilization of wood resources from these fast-growing tree species is limited because little information is available regarding the properties and anatomical characteristics of the wood (Adi et al 2014, Istikowati et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The Southeast Asian region is home to many fastgrowing tree species, typically found in secondary forests after shifting cultivation (Suzuki 1999ab, Adi et al 2014, Istikowati et al 2014. However, utilization of wood resources from these fast-growing tree species is limited because little information is available regarding the properties and anatomical characteristics of the wood (Adi et al 2014, Istikowati et al 2014. These wood characteristics and the corresponding pulp properties have recently been investigated for three unutilized fast-growing tree species-terap (Artocarpus elasticus), medang (Neolitsea latifolia), and balik angin (Alphitonia excelsa), which grow naturally in secondary forests in South Kalimantan-to exploit these potential wood resources as new alternative raw materials for pulp production (Istikowati et al 2016).…”
Section: Introductionmentioning
confidence: 99%